2012
DOI: 10.1155/2012/568351
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Ultrasound Findings in Cornelia de Lange Syndrome: A Case Report

Abstract: Introduction. The objective is to report a case of Cornelia de Lange syndrome (CdLS) diagnosed by detailed observations using three-dimensional sonography. Case Report. A 33-year-old healthy multipara was referred to our hospital at 34-week gestation after severe fetal growth restriction, congenital heart anomaly, and antebrachium abnormality were diagnosed during the third trimester. Further sonography diagnosis on cardiac abnormalities diagnosed the existence of ventricular septal defect in the outflow tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A prenatal diagnosis could be made in 6 cases only. [11][12] Our patient also had a dysmorphic facial appearance and phocomelia on the right.…”
Section: Discussionmentioning
confidence: 70%
“…A prenatal diagnosis could be made in 6 cases only. [11][12] Our patient also had a dysmorphic facial appearance and phocomelia on the right.…”
Section: Discussionmentioning
confidence: 70%
“…Congenital heart diseases have been also reported in ultrasound scan of fetuses affected by CdLS, including ventricular septal defect (Le Vaillant et al, ; Akaori et al, ; Clark et al, ), truncus arteriosus communis (Akaori et al, ), tetralogy of Fallot (Drolshangen et al, ; Clark et al, ), and mild cardiac hypertrophy (Lalatta et al, ). Other cases studied prenatally showed, after birth, congenital heart diseases undetected during the intrauterine life, including severe malformations, such as tetralogy of Fallot (Bruner and Hsia, ; Lalatta, ) and coarctation of the aorta (Chong et al, ).…”
Section: Fetal Malformationsmentioning
confidence: 99%
“…Growth failure is considered a typical characteristic of infants affected by CdLS. Prenatal evidence shows that a reduced rate of growth can also be found during intrauterine life (Westergaard et al, ; Bruner and Hsia, ; Drolshagen et al, ; Cunniff et al, ; Jelsema et al, ; Kliewer et al, ; Pankau and Janig, ; Goolsby et al, ; Manouvrier et al, ; Ackerman and Gilbert‐Barness, ; Ranzini et al, ; Boog et al, ; Sekimoto et al, ; Huang and Porto, ; Marino et al, ; Hulinsky et al, ; Price et al, ; Le Vaillant et al, ; Lalatta et al, ; Chong et al, ; Sepulveda et al, ; Wilmink et al, ; Kanellopoulos et al, ; Akahori et al, ; Spaggiari et al, ): symmetrical intrauterine growth restriction has often been reported, with a trend of fetal abdominal and cephalic circumference that falls below the 10th percentile at approximately 25 weeks of gestation (Kliewer et al, ), but sometimes earlier, at 20 to 21 weeks of gestation (Boog et al, ; Sekimoto et al, ; Le Vaillant et al, ; Price et al, ) or even before the week 20 (Bruner and Hsai, ).…”
Section: Fetal Biometrymentioning
confidence: 99%
See 2 more Smart Citations